Abertura - Maurique, Jorge Antônio; Bruna, Sérgio Varella; Farina, Elizabeth; Kapaz, Emerson; Ferraz Júnior, Tércio Sampaio (Revista do IBRAC, 2024)
JORGE ANTONIO MAURIQUE (Presidente da AJUFE) .................... 7 SÉRGIO VARELLA BRUNA (Presidente do IBRAC) .................... 9 ELIZABETH FARINA (Presidente do CADE) .................... 10 EMERSON KAPAZ (Presidente do ETCO) .................... 12 TÉRCIO SAMPAIO FERRAZ JÚNIOR (Professor Titular da FADUSP) .................... 13